The effect of illusion of control and self attribution on herding behaviour with a moderating role of information availability: a case of retail investors of Pakistan stock exchange - Ahmad Sabir, Saeed; Mohammad, Hisham; Kadir Shahar, Hanita (2018)
Astract Investment behaviour of investors plays essential role in the performance of investment. Normally, investors are unable to gather relevant information which leads investors towards cognitive errors. These errors affect the behaviour of individuals and lead them towards herding the decision of others. Ultimately, investors make wrong investment decision that is a cause of damage the investment of investors. The prime purpose of this paper is to study the effect of factors such as illusion of control and self-attribution on herding behaviour of Pakistan stock exchange's individual investors. A quantitative research approach is used to achieve this objective. Data obtained from 323 retail investors of Pakistan stock exchange via survey questionnaires. Partial Least Squares (PLS) analysis was used to test the hypotheses. The findings indicate that illusion of control and self-attribution are predictors of retail investors' herding behaviour. Furthermore, the results of this study directed that information availability moderate the relationship between cognitive factors and herding behaviour. This study is provided new empirical insights of investors, therefore it is significant for practitioners while making the strategies related to investment in stock market.